Psychosocial experiences of pregnant women during the COVID-19 pandemic: a UK-wide study of prevalence rates and risk factors for clinically relevant depression and anxiety - Semra Worrall; Olivia Pike; Paul Christiansen; Leanne Jackson; Leonardo De Pascalis; Joanne A. Harrold; Victoria Fallon; Sergio A. Silverio (Journal of Psychosomatic Obstetrics and Gynecology)
Purpose: Whilst the antenatal period is well established as a period of increased vulnerability to mental health difficulties, restrictions resulting from COVID-19 lockdown in the UK are likely to have negatively affected psychosocial outcomes in these women.Materials and Methods: This study aimed to describe prevalence rates of clinically relevant antenatal anxiety and depression, and explore whether psychosocial changes as a result of the pandemic were predictive of clinically relevant anxiety and depression. Antenatal women (N = 684) completed an online survey of psychosocial measures during the UK government’s initial lockdown restrictions.Results: Descriptive statistics indicate women experienced high levels of anxiety and depression and that changes resulting from restrictions were perceived negatively. Whilst 11.7% of women reported a current, clinical diagnosis of depression, 47.8% reported a score of ≥13 on the EPDS, indicating clinically relevant depression. Similarly, 18.7% of women reported a current, clinical diagnosis of anxiety, but 68.1% scored ≥40 on the STAI, indicating clinically relevant anxiety. After controlling for known demographic risk factors, only psychosocial change because of COVID-19 restrictions predicted clinically relevant anxiety (28%) and depression (27%).Conclusions: This study highlights the importance of considering antenatal women as a high-priority group, and ensuring antenatal care remains accessible and uninterrupted in any future crises.